Sistema de gerenciamento de pedidos para empresas que atuam com representações e vendas de produtos - Budtinger, Marcos Daniel (2017)
Increasingly, people use online platforms, named software, as part of their day-to-day. Since the emergence of Web 2.0, together with the rapid advance of telecommunications and widespread use of Internet, these platforms have been a business strategy for companies. In light of this, this work presents an online web system for ordering management of any kind of products. The platform was developed by employing technologies such as VRaptor, Bootstrap, HTML5, CSS3, and Apache Ivy. Eclipse was adopted as an Integrated Development Environment (IDE). The main features of the software developed can be summarized as follows: order and customer management, control and calculation of commissions, and reports.